« Fausses porcelaines, vraies innovations ? Tôles vernies, économie de la variété et invention technique dans la seconde moitié du xviiie siècle » - Sébastien Pautet (Les Cahiers de Framespa)
Researchers have often analysed substitutions of Asian products – and especially porcelain – by focusing on connections between markets and product innovation. However, techniques are rarely put on the front stage. This paper studies the production of « fake » painted sheet plate porcelains in Paris during the 1760s and 1770s, to understand the technical background of such innovating substitutions of products. First, it studies how imitation and analogy were a major part of innovation during the 18th century. Then the links between the rise of plating and varnishing techniques and the production of new creative products is highlighted. Finally, this paper demonstrates that these fake porcelains symbolize some of the deep transformations of product innovation in 18th-century France, with the growing role played by finishing techniques.